The Effect of Poultry Manure and Mulch on the Growth and Yield Cayenne Pepper On Alluvial Soils - ,, Yuniarti; ,, Nurjani; Safwan, Mulyadi (Jurnal Sains Pertanian Equator, 2020)
The cultivation of cayenne pepper in alluvial soil has some problems, one of them is the solid structure of the soil. Poultry manure can be used as an alternative to soil structure, whilemulch to reduce nutrient leaching from rain splashes. This study aims to find out the interaction of poultry manure andmulch on the growth and yield of cayenne pepper plants on alluvial soil.This research was conducted in Tengguli village land, Sajad District, Sambas Regency from 18th February to 15th May 2019. This study used a split plot design, is silver plastic mulch (m0= without mulch and m1= mulch) as main plot andpoultry manure (a1= 5 ton/ha, a2= 10 ton/ha, a3= 15 ton/ha) as sub plot. Observation variables were plant height, dry weight of the plants, root volume, number of plant fruit, weight of plant fruit, weight of fruit, number of plot fruit, and weight of plot fruit. The result shows that the interaction poultry manure 15 to/ha and mulch provide the highest ofgrowth and cayenne pepper plant results on alluvial soil. Keyword: Mulch,Poultry Manure, Alluvial Soil, Cayenne Pepper Plants